Embedded Systems -- Modeling, Technology, and Applications Proceedings of the 7th International Workshop held at Technische Universität Berlin, June 26/27, 2006 - Hommel, Günter; Huanye, Sheng (Springer Netherlands : Imprint: Springer, 2006)
The International Workshop on "Embedded Systems - Modeling, Techn- ogy, and Applications" is the seventh in a successful series of workshops that were established by Shanghai Jiao Tong University and Technische Universität Berlin. The goal of those workshops is to bring together - searchers from both universities in order to present research results to an international community. The series of workshops started in 1990 with the International Workshop on Artificial Intelligence and was continued with the International Wo- shop on "Advanced Software Technology" in 1994. Both workshops have been hosted by Shanghai Jiao Tong University. In 1998 the third workshop took place in Berlin. This International Workshop on "Communication Based Systems" was essentially based on results from the Graduiertenk- leg on Communication Based Systems that was funded by the German Research Society (DFG) from 1991 to 2000. The fourth International Workshop on "Robotics and its Applications" was held in Shanghai in 2000. The fifth International Workshop on "The Internet Challenge: Tech- logy and Applications" was hosted by TU Berlin in 2002. The sixth Int- national Workshop on "Human Interaction with Machines" was hosted by Shanghai Jiao Tong University. The subject of this year's workshop has been chosen because the field of Embedded Systems has not only gained major interest in the research community but has also significant economic impact in different appli- tion fields. Mechanic, hydraulic, and electronic control systems are being replaced by microcomputer based embedded systems.